Antibodies to N-homocysteinylated albumin and haemoglobin in patients with rheumatoid arthritis: a potential new marker of disease severity. (January 2014) - Nowakowska-Plaza, A; Potaczek, DP; Gluszko, P; Undas, A
<x xml:space="preserve">Abstract</x> Objectives: To investigate whether anti-Nε-homocysteinylated albumin (anti-N-Hcy-Alb) and haemoglobin (anti-N-Hcy-Hb) antibodies occur in rheumatoid arthritis (RA) and whether they are associated with RA activity and/or severity. Method: Plasma total homocysteine (tHcy) and serum anti-N-Hcy-Alb and -Hb antibodies levels were determined in 76 RA patients (12 men and 64 women, median age 56 years) and 80 age- and sex-matched controls. Results: RA patients compared to healthy controls demonstrated elevated tHcy [median (IQR), 13.20 (3.80) vs. 9.45 (3.25) μmol/L; p < 0.000001] and anti-N-Hcy-Alb and -Hb antibodies [absorbance at 490 nm, median (IQR), 0.546 (0.085) vs. 0.452 (0.056) and 0.649 (0.106) vs. 0.532 (0.057), respectively; all p < 0.000001]. In RA patients, RA radiological class was a strong independent predictor of tHcy [β (SE), 0.59 (0.11); p = 0.000001] and anti-N-Hcy-Alb [0.36 (0.12); p = 0.003] and -Hb [0.49 (0.11); p = 0.00007] antibodies. The number of swollen joints, but not C-reactive protein (CRP), interleukin 6 (IL-6), positive rheumatoid factor (RF), or anti-cyclic citrullinated peptide (anti-CCP) antibodies, showed independent effects on anti-N-Hcy-Alb [β (SE), 0.36 (0.11); p = 0.001] and -Hb [0.25 (0.11); p = 0.02] antibodies. Anti-N-Hcy-Hb antibodies, but not those against N-Hcy-Alb, were positively correlated with RA functional class and RA duration. No effect of any medications on tHcy or anti-N-Hcy-protein antibodies was observed. Conclusions: This study is the first to show that RA is characterized by enhanced autoimmune response to Nε-homocysteinylated proteins detectable in circulating blood, which is related to some clinical measures of RA severity.